Financial Market Development on Economic Growth in Indonesia Using Principal Component Regression Analysis - M Yunus; Budi Setiawan; Priya Rani Bhagat; Adil Saleem (Department of Accounting, Faculty of Economics & Business, 2022)
This study investigates the relationship between macroeconomic variables and financial market development on economic growth in Indonesia using principal component analysis. A quantitative data was collected from World Bank dataset from 2002 to 2019. Data were analysed using statistical software R. Findings reveal principal component analysis is better than multiple linear regression in explaining the correlation among independent and dependent variables. This study also reveals stock traded of total value as percentage of GDP has the biggest effect on the performance on Indonesian economy during research period. In contrast, unemployment has the smallest impact on economic growth in Indonesia. The results assist in understanding the importance of macroeconomic variables and financial market development on the performance of Indonesian economy.